2021
DOI: 10.1002/rmv.2225
|View full text |Cite
|
Sign up to set email alerts
|

Current views on the potentials of convalescent plasma therapy (CPT) as Coronavirus disease 2019 (COVID‐19) treatment: A systematic review and meta‐analysis based on recent studies and previous respiratory pandemics

Abstract: Summary Convalescent plasma therapy (CPT) has been investigated as a treatment for COVID‐19. This review evaluates CPT in COVID‐19 and other viral respiratory diseases, including severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS) and influenza. PubMed and Google scholar databases were used to collect eligible publications until 8 December 2020. Meta‐analysis used Mantel–Haenszel risk ratio (RR) with 95% confidence interval (CI) and pooled analysis for individual patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 134 publications
0
15
0
Order By: Relevance
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram is reported in Figure 1 . After the full texts were scrutinized against the inclusion and exclusion criteria, 29 SRs were included in the umbrella review [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and 23 SRs were excluded [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram is reported in Figure 1 . After the full texts were scrutinized against the inclusion and exclusion criteria, 29 SRs were included in the umbrella review [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and 23 SRs were excluded [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , …”
Section: Resultsmentioning
confidence: 99%
“…Of the 29 SRs included in the overview, 26 were focused exclusively on COVID-19 [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], while three were focused on respiratory pandemics and on beta coronaviruses infections [ 10 , 19 , 30 ]. Two SRs [ 17 , 22 ] were a subgroup analysis of other reviews [ 16 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…63 Convalescent plasma was used in previous outbreak of other emerging infectious diseases, such as influenza, Ebola, SARS and MERS. 64,65 Given the theoretical effects, rapid availability and previous experience in treatment of other infectious diseases, convalescent plasma has been used to treat COVID-19 since the beginning of the outbreak. There have been numerous observational studies as well as 10 RCTs [66][67][68][69][70][71][72][73][74][75] comparing the effects and safety of convalescent plasma and placebo/standard care.…”
Section: Convalescent Plasmamentioning
confidence: 99%
“…Convalescent plasma from recovered COVID‐19 patients is postulated to have neutralizing antibodies and provide passive immunity 63 . Convalescent plasma was used in previous outbreak of other emerging infectious diseases, such as influenza, Ebola, SARS and MERS 64,65 . Given the theoretical effects, rapid availability and previous experience in treatment of other infectious diseases, convalescent plasma has been used to treat COVID‐19 since the beginning of the outbreak.…”
Section: Anti‐viral Therapiesmentioning
confidence: 99%